Analysis of Mekarbuana Tourism Marketing Strategies to Increase Tourist Visit Interest : Case Study of Mekarbuana Tourism Management in Karawang - Neni Sumarni; Jaja Suteja; Juanim Juanim (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Tourism is a type of business in the service sector. As a business, it requires the formulation of an appropriate marketing strategy to ensure its sustainability. The purpose of this study was to determine the marketing strategy of Mekarbuana Tourism to increase visitor interest. The study was conducted with Mekarbuana Tourism managers, using descriptive qualitative research through a SWOT analysis. The results showed that Mekarbuana Tourism's marketing strategy needs to be developed using a diversification strategy through various programs and policies such as digital promotion, training and mentoring for managers in developing tourism products, and developing educational tourism. Cooperation between institutions is also necessary for the strategy to be implemented effectively. Mekarbuana Tourism managers need a joint commitment with tourism awareness groups, village officials, and the Karawang Regency government to support their efforts to increase visitor interest.